Mitigasi Non Revenue Water (NRW) Sistem Jaringan Distribusi pada District Meter Area (DMA) Zona Kota Blahbatuh PDAM Gianyar - Yekti, Mawiti Infantri; Gede Pebriarta Pratama, Ida Bagus; Ngurah Purbawijaya, Ida Bagus (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
The most common problem with drinking water supply is Non Revenue Water (NRW). NRW can be grouped into two types, namely physical water loss and non-physical water loss. This study aims to determine the NRW size, NRW causes, counter measures that can be done to suppress NRW. The results of evaluation of distribution networks that occur in the Blahbatuh City Zone District Meter Area (DMA) PDAM Gianyar. The difference between the amount of water distributed and the amount of water recorded in the account is NRW. The way to find out the cause and control of NRW is to analyze the results of the step test, UFM test (Ultrasonic Flow Meter), and conduct the interviews with employees of PDAM. The evaluation of distribution networks is only done in DMA Pande that has completed data. The amount of NRW that occured in the Blahbatuh City Zone is 474,142.83 m3/year (59.91%). The water loss is caused by damage to pipe accessories, leaky pipes, inaccuracies in the accuracy of the water meter. The water loss can be overcame by establishing a DMA, replacing pipe accessories, calibrating and replacing water meters. The evaluation results for the existing conditions of the distribution network in DMA Pande of Blahbatuh City Zone have not worked optimally. It seen from the results of the waternet and from the number of SR’s that have not met the requirements for the formation of a DMA.